Pengaruh Employee Engagement Dan Kompensasi Sebagai Upaya Peningkatan Kerja (Studi Pada Karyawan PT Bank BRI KCP Helvetia) - Chairul Azmi Puteh; Nana Dyki Dirbawanto; Onan Marakali Siregar (CV Edujavare Publishing, 2024)
Employee performance improvement is the key to a company's success. This work improvement is influenced by several factors, two of which are the provision of appropriate job descriptions as part of employee engagement and appropriate compensation by the company. However, employees of BRI Branch Office (KCP) Helvetia consider that the company has not provided job descriptions or compensation as they should. This then hinders employee performance improvement. The researcher uses Employee Engagement, Compensation, and Work Improvement as research variables. This study aims not only to solve the problems that occur at BRI KCP Helvetia but also to determine the level of relationship between the three variables and the level of influence of the first two variables on the Work Improvement variable. This study was conducted using a quantitative method with an associative approach. Research data were collected by distributing questionnaires to all employees with support from relevant studies. The data were then analyzed using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The researcher found that Employee Engagement and Compensation are closely related and have a significant effect on Work Improvement both individually and simultaneously with a level of relationship and influence of 90.2% and 80.1%. The results of the study show that job desk and compensation are two main components that can facilitate the improvement of employee performance at BRI KCP Helvetia.